MEDIUM TO LONG TERM OUTCOME OF PATIENTS TREATED WITH RADICAL RETROPUBIC PROSTATECTOMY FOR CLINICALLY LOCALIZED PROSTATE CANCER - Nazim, Syed Muhammad; Nadeem, Mehwash; Farooqui, Nuzhat; Abbas, Farhat (Journal of Ayub Medical College Abbottabad, 2016)
Objective: To evaluate the medium to long term cancer control, morbidity, mortality and functional outcome in men undergoing open radical retro pubic prostatectomy (RP) and pelvic lymph node dissection (PLND) for clinically localized adenocarcinoma prostate (CaP). Methods: A total of 200 patients were operated with intention to treat for localized CaP, between January 1998 to October 2013. Patients' characteristics, operative data, progression-free survival rate, recurrence rate, morbidity, mortality and functional outcome were analyzed. Statistical analysis was done using SPSS v.19. Kaplan Meir curve was plotted for survival estimate. Results: The mean age was 63.6 + 6.2 years and median pre-operative PSA was 11+ 2.1 ng/ml. RP and bilateral PLND were performed in 172 patients of which 35 (20%) had nerve-sparing surgery. In 8 cases with gross lymph node metastasis at frozen section, only bilateral orchiectomy was done while remaining 20 patients had RRP+PLND with bilateral orchiectomy. The final study population was therefore 192. Mean length of hospital stay was 6 + 1 day with zero 30-day perioperative mortality. On final histopathology, 78% of tumors were confined to the prostate gland. Twenty four (12.5%) patients had positive surgical margins. Overall, 163 (85%) patients regained full continence. Nearly half of patients with nerve sparing approach were potent without any supportive measures. Most common long term complication was urethral stricture (8%). At median follow up of 41 months, the progression-free and overall survival rates were 85% and 94%, respectively. Seven percent had biochemical recurrence while 4% had local recurrence and 4% had metastatic disease. Conclusions: Our results indicate that RP has an excellent potential for cancer control and functional outcome with low morbidity in men with localized CaP. Our data is consistent with larger data from other centers around the world. Background: To evaluate the medium to long term cancer control, morbidity, mortality and functional outcome in men undergoing open radical retro pubic prostatectomy (RP) and pelvic lymph node dissection (PLND) for clinically localized adenocarcinoma prostate (CaP). Methods: A total of 200 patients were operated with intention to treat for localized CaP, from January 1998 to October 2013. Patients' characteristics, operative data, progression-free survival rate, recurrence rate, morbidity, mortality and functional outcome were analysed. Statistical analysis was performed using SPSS v.19. Kaplan Meir curves were plotted for survival estimate. Results: The mean age was 63.6±6.2 years and median pre-operative PSA was 11±2.1 ng/ml. RP and bilateral PLND were performed in 172 patients of which 35 (20%) had nerve-sparing surgery. In 8 cases with gross lymph node metastasis at frozen section, only bilateral orchiectomy was done while remaining 20 patients had RRP+PLND with bilateral orchiectomy. The final study population was therefore 192. Mean length of hospital stay was 6±1 day with zero 30-day perioperative mortality. On final histopathology, 78% of tumours were confined to the prostate gland. Twenty four (12.5%) patients had positive surgical margins. Overall, 163 (85%) patients regained full continence. Nearly half of patients with nerve sparing approach were potent without any supportive measures. Most common long term complication was urethral stricture (8%). At median follow up of 41 months, the progression-free and overall survival rates were 85% and 94%, respectively. Seven percent had biochemical recurrence while 4% had local recurrence and 4% had metastatic disease. Conclusions: Our results indicate that RP has an excellent potential for cancer control with low morbidity and good functional outcome in men with localized CaP. Our data is consistent with larger series from other centres across the globe. Keywords: Prostate Cancer; Radical Prostatectomy; Long term outcome